2014
DOI: 10.1371/journal.pone.0111927
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Mcl-1L Splice Variant Is Associated with Poor Prognosis and Chemoresistance in Oral Cancers

Abstract: BackgroundAltered expression of Mcl-1, an anti-apoptotic member of the Bcl-2 family, has been linked to the progression and outcome of a variety of malignancies. We have previously reported the overexpression of Mcl-1 protein in human oral cancers. The present study aimed to evaluate the clinicopathological significance of the expression of three known Mcl-1 isoforms in oral tumors and the effect of targeting Mcl-1L isoform on chemosensitivity of oral cancer cells.MethodsThe expression of Mcl-1 isoforms- Mcl-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…2b). The probe for MCL-1L also detects MCL-1ES but the later is likely expressed at much lower levels than MCL-1L and MCL-1S as reported previously (Kim 2009; Kim and Bae 2013; Palve et al 2014). These data show the up-regulation of MCL-1/ES transcripts following transfection of miR-29b in intestinal fibroblasts.
Fig.
…”
Section: Resultssupporting
confidence: 70%
“…2b). The probe for MCL-1L also detects MCL-1ES but the later is likely expressed at much lower levels than MCL-1L and MCL-1S as reported previously (Kim 2009; Kim and Bae 2013; Palve et al 2014). These data show the up-regulation of MCL-1/ES transcripts following transfection of miR-29b in intestinal fibroblasts.
Fig.
…”
Section: Resultssupporting
confidence: 70%
“…Besides breast cancer (43), overexpression of MCL1 has been associated with survival pathways, resistance, and poor prognosis in multiple cancers, such as melanoma (20), small-cell lung cancer (44), colorectal cancer (45), oral cancers (46), endometrial cancer (47), as well as multiple hematological malignancies (21,48). Therefore, our combination treatment may be effective in other cancers increasing the impact of this study.…”
Section: Discussionmentioning
confidence: 99%
“…15 Several studies have also shown that MCL-1 is a barrier to therapeutic sensitivity, including those that target BCL-2 (reviewed in 16 ). MCL-1 is responsible for therapeutic resistance in a range of cancers including oral cancers, 17 lung cancer, 18 pancreatic cancer, 19 ovarian cancer, colon cancer 20 and triple negative breast cancer. 21 MCL-1 also confers the survival of breast cancer cells in vitro 22 and protects HER-2 positive breast cancers from hypoxia-induced death.…”
Section: Mcl-1 Is Important For Cancer Cell Survival and Therapeutic mentioning
confidence: 99%